2013
DOI: 10.3389/fendo.2013.00063
|View full text |Cite
|
Sign up to set email alerts
|

Hatching the Cleidoic Egg: The Role of Thyroid Hormones

Abstract: A major life stage transition in birds and other oviparous sauropsids is the hatching of the cleidoic egg. Not unlike amphibian metamorphosis, hatching in these species can be regarded as a transition from a relatively well-protected “aqueous” environment to a more hazardous and terrestrial life outside the egg, a transition in which thyroid hormones (THs) (often in concert with glucocorticoids) play an important role. In precocial birds such as the chicken, the perihatch period is characterized by peak values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 86 publications
3
31
0
Order By: Relevance
“…Several studies on altricial birds have suggested the absence of a distinct perihatch peak for the plasma thyroid hormone [1216]. Typically, the concentration of circulating thyroid hormone increases gradually to reach levels typically recorded in adult in approximately 3–4 weeks post-hatching [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on altricial birds have suggested the absence of a distinct perihatch peak for the plasma thyroid hormone [1216]. Typically, the concentration of circulating thyroid hormone increases gradually to reach levels typically recorded in adult in approximately 3–4 weeks post-hatching [16].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the concentration of circulating thyroid hormone increases gradually to reach levels typically recorded in adult in approximately 3–4 weeks post-hatching [16]. In contrast to precocial birds, altricial birds hatch with their eyes and ears closed and show less locomotor activity [1].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the perihatching period in chickens is characterized by a thyroid hormone peak approaching a ninefold increase when internal pipping is initiated [2]. At pipping, the chicken fetus switches from only chorioallantoic to a combined pulmonary-chorioallantoic respiration that lasts through hatching.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones are essential for normal development and play a crucial role in developmental processes in vertebrates, including humans and birds [1,2]. During the middle and last trimester, corticosteroids and thyroid hormones cooperate to promote sufficient lung maturation and surfactant production for survival of the newborn [3].…”
Section: Introductionmentioning
confidence: 99%
“…This marked decrease in D3 activity is accompanied by a plasma T 3 surge, which suggests that the decrease in hepatic D3 activity leads to the elevation of plasma T 3 level ( Van der Geyten et al, 1997). The increase in plasma T 3 has been found indispensable to advance a number of processes for normal hatching of chicken embryos (De Groef et al, 2013).…”
Section: ©2017 Reviews In Agricultural Sciencementioning
confidence: 99%